UPAYA MENINGKATKAN KETERAMPILAN KOMUNIKASI SISWA MELALUI MODEL PEMBELAJARAN THINK-TALK-WRITE - Nurlailasari, Ratih; Enawaty, Eny; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:The purpose of this study is to improve students' communication skills using Think-Talk-Write learning model on buffer solution material in SMA Muhammadiyah 2 Pontianak. The method of this research is Classroom Action Research. The completed research was implemented to the first semester of eleventh grade students in SMA Muhammadiyah 2 Pontianak there where 36 students from XI IPA class of academic year 2014/2015. The implementation of this research through two cycles, each cycle consists of one meeting with the time allocation of each meeting is 2 x 45 minutes. Cycle I consists of the consept and buffer solution concept, while cycle II consists of pH value of buffer solution. Communication skills in this study include group discussions, asking questions, responding to peer presentation and drawing conclusions. The research instrument was the observation sheet of the learning process and the communication skill observation sheet. The result of communication skill shows that cycle I is 27,08% and cycle II shows 56,94%, it can be concluded that learning using Think-Talk-Write model can be used to improve students communication skill. Â Â Keywords: Think-Talk-Write, Communication Skills